Mature T/NK‐Cell lymphomas of the oral and maxillofacial region: A multi‐institutional collaborative study. (29th June 2021) - de Arruda, José Alcides Almeida; Abrantes, Thamiris de Castro; Cunha, John Lennon Silva; Roza, Ana Luiza Oliveira Corrêa; Agostini, Michelle; Abrahão, Aline Corrêa; Canedo, Nathalie Henriques Silva; Ramos, Denize D'Azambuja; Milito, Cristiane Bedran; Pontes, Flávia Sirotheau Correa; Pontes, Hélder Antônio Rebelo; Barra, Marinez Bizarro; et al.
Abstract: Background: The diagnosis of oral and maxillofacial mature T/NK‐cell neoplasms is challenging because of their rarity, morphological heterogeneity and complex immunophenotype with scarce available data describing their clinical and microscopic aspects. Therefore, in this study, we investigated a series of mature T/NK‐cell neoplasms affecting this anatomical region and provided an updated literature review. Methods: Cases diagnosed as mature T/NK‐cell lymphomas affecting the oral and maxillofacial region were retrospectively retrieved from six pathology files and their diagnoses were confirmed using haematoxylin and eosin‐stained slides, immunohistochemical reactions and in situ hybridization for Epstein‐Barr virus (EBV) detection. Patients' clinical data were collected from their pathology forms. Results: A total of 22 cases were included in this study. Eleven (50%) consisted of extranodal NK/T‐cell lymphomas, nasal type; eight (36.4%) were peripheral T‐cell lymphomas, NOS; two (9.1%) were adult T‐cell leukaemia/lymphomas, and one (4.5%) was an ALK‐positive anaplastic large cell lymphoma. Overall, males predominated, with a mean age of 55.7 years. The palate was the most affected site (50%), and tumours usually presented as destructive and painful ulcers. EBV was present in all cases of extranodal NK/T‐cell lymphoma nasal type but was absent in the other subtypes. Conclusion: Among mature T/NK‐cell lymphomas of the oral and maxillofacial region, extranodal NK/T‐cell lymphoma, nasal type and peripheral T‐cell lymphoma, NOS predominated. Older men were the most affected patients, and this heterogeneous group of neoplasms has a very aggressive clinical behaviour.